Sharpening Logical Thinking Ability Through Game Application Development Activities in Adolescents - Yufis Azhar; Dwi Anggraini Puspita Rahayu; Wildan Suharso (Jurnal Perempuan dan Anak, 2020)
One of the main capitals in the era of industry 4.0 is creative Human Resources. Creativity here means the ability to always innovate and be able to provide intelligent solutions of problems that arise in the community. Youth as the nation's greatest asset must continue to be encouraged to hone its creativity. Developing game apps is one way to hone this creativity. Because when creating a game app, one is required to imagine, but it remains logical. Hisbul Wathan, as one of the scouting organizations in Indonesia, which fosters the younger generation, is expected to play an active role in the development of Industry 4.0. Therefore, in this Community Service activity, will be given training on the creation of game applications to hone the logical thinking skills of hisbul wathan scouting movement cadres, especially for Kwarda Kota Batu.